2021
DOI: 10.1039/d1cs00600b
|View full text |Cite
|
Sign up to set email alerts
|

Covalent organic frameworks as multifunctional materials for chemical detection

Abstract: This review highlights how the unique properties of COFs are harnessed to develop different types of chemical detection systems based on the principles of chromism, luminescence, electrical transduction, chromatography, spectrometry, and others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
103
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(103 citation statements)
references
References 444 publications
0
103
0
Order By: Relevance
“…192,193 There have been many breakthrough applications for this technology in batteries. 192,[194][195][196][197][198][199] Wang et al 200 reported a new metalo-covalent organic framework doped with Ag/Ag 2 O. This MCOF combines the advantages of MOFs and COFs and provides excellent OER and ORR performance through synergistic interaction between Co, O, N, Ag/Ag 2 O and a nano-ower-like structure, as shown in Fig.…”
Section: Organic-based Framework Air Electrodementioning
confidence: 99%
“…192,193 There have been many breakthrough applications for this technology in batteries. 192,[194][195][196][197][198][199] Wang et al 200 reported a new metalo-covalent organic framework doped with Ag/Ag 2 O. This MCOF combines the advantages of MOFs and COFs and provides excellent OER and ORR performance through synergistic interaction between Co, O, N, Ag/Ag 2 O and a nano-ower-like structure, as shown in Fig.…”
Section: Organic-based Framework Air Electrodementioning
confidence: 99%
“…103–106 Generally, COFs are chemically stable in water and organic solvents as well as under acidic, alkaline, and oxidizing conditions. These features enable the use of COFs as functional materials for various applications under different conditions, including for adsorption and separation, 107–111 catalysis, 112–115 nanomedicine, 116–120 sensing, 121–124 photochemistry, 125 electrochemistry, 126 energy storage, 127 and many others.…”
Section: Introductionmentioning
confidence: 99%
“…Today, more and more emerging materials (graphene [ 1 , 2 , 3 , 4 , 5 ], perovskite [ 6 , 7 , 8 , 9 , 10 ], etc.) with special structures (MOF [ 11 , 12 , 13 , 14 , 15 ], COF [ 16 , 17 , 18 , 19 , 20 ], etc.) are appearing on the horizon, and their properties are yet to be explored and improved.…”
Section: Introductionmentioning
confidence: 99%